Patients' reflections on prehospital symptom recognition and timely treatment of myocardial infarction. (17th January 2021) - Fålun, Nina; Langørgen, Jørund; Fridlund, Bengt; Pettersen, Trond; Rotevatn, Svein; Norekvål, Tone M
Abstract: Aims: Early treatment is crucial to successful therapy in patients with acute myocardial infarction (MI). Prehospital delay is associated with increased morbidity and mortality. There is little empirical evidence of patients' reflections on prehospital symptoms of MI and timely treatment at the time of discharge from hospital. To explore patients' reflections on prehospital symptoms of MI and their experiences of interaction with local hospitals, general practitioners, and laypersons. Methods and results: An inductive explorative design with a qualitative method approach was used to conduct in-depth interviews of patients after confirmed MI. Twenty patients were purposefully selected based on age and gender. Face-to-face, semi-structured interviews were conducted prior to hospital discharge. The interviews were organized around a set of predetermined, open-ended questions, transcribed verbatim and analysed using qualitative content analysis. There were patients who acted upon severe symptoms of MI by seeking medical assistance. Patients commonly experienced that the time from the onset of symptoms to treatment posed a transitional challenge. They did not take subtle signs of MI seriously; they underestimated symptoms of MI and delayed seeking medical assistance. Patients frequently experienced that healthcare professionals did not take them seriously, as they struggled to gain access to healthcare services. Conclusion: This study highlights patients' unique experiences of the pathway from symptom onset to confirmed MI. Severe chest pain is associated with MI and triggers an immediate need for care. However, patients often underestimated moderate chest pain or subtle signs and symptoms of MI. Existing knowledge gaps concerning the misinterpretation of symptoms in primary care need to be addressed in order to reduce this clinical challenge.